IMPLEMENTATION OF DIVERSITY IN THE HANDLING OF CRIMINAL ACTS OF CHILDREN IN THE LEGAL AREA OF MAKASSAR POLRESTABES - Muh. Chaerul Anwar; Hambali Thalib; Hasbuddin Khalid (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal